Corporate Level Software Management - Cooper, J.D. (IEEE transactions on software engineering, 1978)
Software management is considered from the corporate headquarters viewpoint. This perspective encompasses all facets of management, but specifically dealt with are those that are brought to bear on software management obstacles and ways to cope with them are presented. Standardization is presented as the most effective management device available at the corporate level for enhancing the overall software posture. Corporate management actions available for favorably influencing the quality of software over its life cycle and research initiatives are described.